Of tanks and tankies: what's ‘left’ for geography after the invasion of Ukraine - Klinke, I (Wiley, 2023)
This commentary explores the degree to which the 2022 Russian invasion of Ukraine has posed a challenge for political geographers. I reason that while the war has exposed conceptual weaknesses and political blind spots, it has also validated many of the foci with which geographers have approached post-Cold War European security. By drawing attention to the epistemological and moral problems of current NATO scepticism, I argue that tactics of counter-mapping and whataboutery need to be carried out with the necessary care for the historical and political context.